Ethnographies of Moral Reasoning
X, 206 p.
Keywords: Rather than measure the actions of their subjects by reference to either universal rationality or cultural relativism, contributors in this volume describe ordinary people as they value human relationships and reason through the commonplace contradictions of their local way of life in a global age.